Microcephaly proteins Wdr62 and Aspm define a mother centriole complex regulating centriole biogenesis, apical complex, and cell fate - Jayaraman, D; Kodani, A; Gonzalez, D; Mancias, J; Mochida, G; Vagnoni, C; Johnson, J; Krogan, N; Harper, J; Reiter, J; Yu, T; Bae, B; et al. (Cell Press, 2016)
Mutations in several genes encoding centrosomal proteins dramatically decrease the size of the human brain. We show that Aspm (abnormal spindle-like, microcephaly-associated) and Wdr62 (WD repeat-containing protein 62) interact genetically to control brain size, with mice lacking Wdr62, Aspm, or both showing gene dose-related centriole duplication defects that parallel the severity of the microcephaly and increased ectopic basal progenitors, suggesting premature delamination from the ventricular zone. Wdr62 and Aspm localize to the proximal end of the mother centriole and interact physically, with Wdr62 required for Aspm localization, and both proteins, as well as microcephaly protein Cep63, required to localize CENPJ/CPAP/Sas-4, a final common target. Unexpectedly, Aspm and Wdr62 are required for normal apical complex localization and apical epithelial structure, providing a plausible unifying mechanism for the premature delamination and precocious differentiation of progenitors. Together, our results reveal links among centrioles, apical proteins, and cell fate, and illuminate how alterations in these interactions can dynamically regulate brain size.